Determinants of patients at risk of developing obstructive sleep apnea in a primary care clinic - Mohd Radzniwan A Rashid; Saharuddin Ahmad; Aida Jaffar; Fairuz Ali; Norliza Paidi (Hilaris Publishing, 2024)
Introduction Obstructive sleep apnea (OSA) is associated with multiple medical and psychosocial impacts. Current evidence on individuals at risk of developing OSA in Malaysia particularly at primary care setting is scarce. This study aimed to determine the magnitude of patients at risk of developing OSA attended an suburban primary care clinic and associated factors in southern Malaysia.